Atomic Layer Deposition of Intermetallic Co3Sn2 and Ni3Sn2 Thin Films. Issue 3 (16th October 2018) - Väyrynen, Katja; Hatanpää, Timo; Mattinen, Miika; Mizohata, Kenichiro; Meinander, Kristoffer; Räisänen, Jyrki; Link, Joosep; Stern, Raivo; Ritala, Mikko; Leskelä, Markku
Abstract: Intermetallics form a versatile group of materials that possess unique properties ranging from superconductivity to giant magnetoresistance. The intermetallic Co–Sn and Ni–Sn compounds are promising materials for magnetic applications as well as for anodes in lithium‐ and sodium‐ion batteries. Herein, a method is presented for the preparation of Co3 Sn2 and Ni3 Sn2 thin films using diamine adducts of cobalt(II) and nickel(II) chlorides, CoCl2 (TMEDA) and NiCl2 (TMPDA) (TMEDA = N, N, N ′, N ′‐tetramethylethylenediamine, TMPDA = N, N, N ′, N ′‐tetramethyl‐1, 3‐propanediamine) combined with tributyltin hydride. The films are grown by atomic layer deposition (ALD), a technique that enables conformal film deposition with sub‐nanometer thickness control. The Co3 Sn2 process fulfills the typical ALD qualifications, such as self‐limiting growth, excellent film uniformity, and conformal coverage of a trench structure. X‐ray diffraction (XRD) shows reflections characteristic to the hexagonal Co3 Sn2 phase, which confirms that the films are, indeed, intermetallic instead of being mere alloys of Co and Sn. The films are extremely pure with impurity levels each below 1.0 at.%. Ni3 Sn2 films similarly exhibit the expected XRD reflections for the intermetallic phase and are of high purity. The Co3 Sn2 film show magnetic hysteresis with high coercivity values exceeding 500 Oe, indicating great potential in terms of applicability of the films. Abstract : Intermetallic Co3 Sn2 and Ni3 Sn2 are promising materials for Li‐ and Na‐ion batteries and magnetic devices. By combining diamine adducts of cobalt(II) and nickel(II) chlorides with tributyltin hydride, it is possible to prepare Co3 Sn2 and Ni3 Sn2 thin films using atomic layer deposition (ALD). As a precise and controllable method, ALD offers a significant improvement to the previous ways of preparing intermetallics.